RECURRING THEMES IN THE DEBATE ABOUT EUTHANASIA AND ASSISTED SUICIDE - Boer, Theodoor Adriaan (Journal of religious ethics, 2007)
During the past four decades, the Netherlands played a leading role in the debate about euthanasia and assisted suicide. Despite the claim that other countries would soon follow the Dutch legalization of euthanasia, only Belgium and the American state of Oregon did. In many countries, intense discussions took place. This article discusses some major contributions to the discussion about euthanasia and assisted suicide as written by Nigel Biggar (2004), Arthur J. Dyck (2002), Neil M. Gorsuch (2006), and John Keown (2002). They share a concern that legalization will undermine a society's respect for the inviolability and sanctity of life. Moreover, the Report of the House of Lords Select Committee on the Assisted Dying for the Terminally Ill Bill (2005) is analyzed. All studies use ethical, theological, philosophical, and legal sources. All these documents include references to experiences from the Netherlands. In addition, two recent Dutch documents are analyzed which advocate further liberalization of the Dutch euthanasia practice, so as to include infants (Groningen Protocol, NVK 2005) and elderly people “suffering from life” (Dijkhuis Report, KNMG 2004).